The Robin problem for bending of elastic plates. (5th October 2018) - Constanda, Christian; Doty, Dale
Abstract : The solution of the Robin problem in a finite domain for the system of equations modeling the bending of elastic plates with transverse shear deformation is approximated by means of a generalized Fourier series method closely connected to the structure of the boundary integral equation treatment of the problem. The theory is exemplified by numerical computation that shows a high degree of accuracy and efficiency.